Community Economic Empowerment for the Creation of Self-Sufficient Villages - Suyanto; Rahmawati Erma Standsyah; Dendy Syahru Ramadhan (Help: Journal of Community Service, 2024)
Community empowerment is a strategic effort aimed at improving the knowledge and skills of individuals within a community to foster self-reliance and sustainable development. This study focuses on an empowerment initiative conducted in Blarang Village, Tutur District, Pasuruan Regency, chosen for its potential to become an independent village. The empowerment program was structured in two phases: material counseling and focus group discussions (FGDs). Material counseling sessions provided theoretical insights, while the FGDs facilitated interactive discussions to identify local challenges and solutions. The activities resulted in increased knowledge and skills among the participants, as evidenced by their engagement and feedback during both the counseling and discussion sessions. Key topics included agriculture, entrepreneurship, and community organization, which are crucial for the village's progress towards independence. The empowerment initiative demonstrated that structured educational programs could positively impact community self-sufficiency. By actively participating in the process, the community members expressed optimism about applying the skills and knowledge gained to enhance their village’s development. The program succeeded in providing the community with tools and strategies to work towards becoming an independent village. These efforts can serve as a model for similar rural development projects aimed at empowering communities to achieve self-reliance.